SCREENING SCALES FOR THE ASSESSMENT OF COGNITIVE DISORDERS IN CHRONIC CEREBROVASCULAR PATHOLOGY (Modern education and development, 2025)
Currently, with the progressive trend towards an increase in human life expectancy, the number of patients with various degrees of cognitive impairment, including dementia, in the clinical picture of the disease has increased significantly. These disorders have a significant impact on the quality of life of both the patient and his relatives. Therefore, it is extremely important to identify and differentiate cognitive defects as early as possible in order to start active treatment of patients with cognitive disorders at the pre-dementia stage (mild and severe moderate violations). For this purpose, it is advisable to use screening neuropsychological scales in the examination of each patient with vascular pathology complaining of memory and attention disorders.